The Evolution and Role of the Bursal Acromial Reconstruction. Issue 2 (March 2021) - Curtis, Daniel M.; Pullen, W. Michael; Helenius, Kevin; Freehill, Michael T.
Background: Massive, irreparable rotator cuff tears (RCTs) remain a challenging clinical problem with numerous described treatment options. Bursal acromial reconstruction (BAR) represents a promising and evolving technique for a subset of patients with irreparable RCTs. Indications: BAR is indicated for patients with massive, irreparable RCTs with a primary complaint of pain, well-compensated shoulder function, and minimal radiographic degenerative changes of the glenohumeral joint as an alternative to reverse total shoulder arthroplasty or superior capsular reconstruction. Technique Description: Positioning per surgeon preference and diagnostic arthroscopy is performed. Subacromial decompression with a minimal and gentle acromioplasty is performed, followed by assessment of RCT repairability. If the tear is deemed irreparable, acromial measurements in the medial-lateral and anterior-posterior dimensions are obtained. Two pieces of acellular dermal allograft are cut to the acromial dimensions and affixed together using fibrin glue. The reactive side (facing the acromion), medial, and anterior sides of the graft are labeled. Two suture tapes are passed through the corners of the graft and self-locked and run diagonally in a cruciate configuration using an antegrade suture passer. Medial and lateral #2 fiberwire sutures are placed in a luggage-tag configuration. Neviaser (posterior), middle, and anterior acromioclavicular joint portals are created for medial sided suture passage. Medial graft sutures are shuttled through the respective medial portals and the graft is pulled into the subacromial space. The lateral sutures are then removed from percutaneous posterolateral, middle lateral, and anterolateral portals along the acromial edge. Medial sutures are retrieved using a suture grasper subcutaneously on top of the acromion through the percutaneous lateral portals. The sutures are tied through the lateral portals, starting with the medial-lateral sutures, and the knots are buried. Postoperatively, patients are progressed through passive, active-assisted, and active range of motion between weeks 2 and 6 and strengthening is progressed at 6 weeks. Results: Clinical results are lacking in the literature, but anecdotal results in our institution have demonstrated promising early outcomes. Discussion/Conclusion: BAR represents a promising alternative in the array of surgical options for treatment of irreparable RCTs. Graphical Abstract This is a visual representation of the abstract.